Diagnostic Value of Measuring Platelet Von Willebrand Factor in Von Willebrand Disease. - Alessandra Casonato (PLoS ONE, 2016)
Von Willebrand disease (VWD) may be caused by an impaired von Willebrand factor (VWF) synthesis, its increased clearance or abnormal function, or combinations of these factors. It may be difficult to recognize the different contributions of these anomalies. Here we demonstrate that VWD diagnostics gains from measuring platelet VWF, which can reveal a defective VWF synthesis. Measuring platelet VWF revealed that: severe type 1 VWD always coincided with significantly lower platelet and plasma VWF levels, whereas mild forms revealed low plasma VWF levels associated with low or normal platelet VWF levels, and the latter were associated with a slightly shorter VWF survival; type Vicenza (the archetype VWD caused by a reduced VWF survival) featured normal platelet VWF levels despite significantly reduced plasma VWF levels; type 2B patients could have either normal platelet VWF levels associated with abnormal multimer patterns, or reduced platelet VWF levels associated with normal multimer patterns; type 2A patients could have reduced or normal platelet VWF levels, the former associated mainly with type 2A-I, the latter with type 2A-II; plasma and platelet VWF levels were normal in type 2N, except when the defect was associated with a quantitative VWF mutation. Our findings show that measuring platelet VWF helps to characterize VWD, especially the ambiguous phenotypes, shedding light on the mechanisms underlying the disorder.